Performance Measurement Through Balanced Scorecard Approach - Lukman Chalid; Darwis Lannai; Muhammad Syafi'i A. Basalamah (Pusat Penerbitan dan Publikasi Ilmiah, Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2021)
The purpose of this research is to assess the performance of health centers using the Balanced Scorecard (BSC) framework from four perspectives: the customer perspective, the internal process perspective, the learning and growth perspective, and the financial perspective. The BSC application is intended to measure organizational performance from a variety of perspectives, not just financial ones; there must be a balance of financial and non-financial perspectives. This means that BSC is a strategic approach to evaluating an organization's performance that balances the interests of various stakeholders by balancing short- and long-term objectives.